The impact of structured self-management interventions on stroke patients' quality of life - Widiharti Widiharti; Diah Jerita Eka Sari (Universitas Aisyiyah Yogyakarta, 2026)
Stroke causes long-term physical, psychological, and social disability that lowers quality of life. This study evaluated the effectiveness of structured self-management interventions in improves quality of life among stroke patients. In a one-group pretest–posttest design, 50 purposively sampled stroke patients completed a six-week self-management program including health education, individualized goal setting, self-monitoring, and guided support. Quality of life was measured before and after the intervention using the Stroke-Specific Quality of Life (SS-QoL) instrument. The total SS-QoL score was used for statistical analysis, while quality of life categories were used only for descriptive interpretation. Data were analyzed using the Wilcoxon Signed-Rank Test because the paired pretest and posttest total scores were not normally distributed. The results showed a significant increase in total SS-QoL scores after the intervention (p < 0.001). Descriptively, before the intervention, most participants were in the poor and very poor quality of life categories, whereas after the intervention most participants shifted to the good and very good categories. The largest gains were seen in physical function, independence in daily activities, and reductions in emotional distress. A six-week self-management intervention produced significant, clinically meaningful improvements in quality of life among these stroke patients. Integrating structured self-management into routine poststroke care may enhance recovery; randomized trials and longer follow-up are recommended to confirm these findings.